2005
DOI: 10.1103/physrevb.72.024454
|View full text |Cite
|
Sign up to set email alerts
|

Role of disorder in phase coexistence in manganites: Noise in layered films

Abstract: Films of La 2/3 Ca 1/3 MnO 3 were prepared via atomic layer-by-layer epitaxy both as standard solid-solution alloys and as A-site-ordered superlattices of LaMnO 3 and CaMnO 3 layers. The transport properties were similar, although with a shifted and broadened metal-insulator transition temperature T C in the ordered material. Transport noise near T C was also similar, in both cases revealing a narrow peak in noise magnitude versus temperature. The phase coexistence region near T C has little dependence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Intermixing of Sr atoms into the LMO layer is not likely in these samples because the kinetics of atomic diffusion perpendicular to the surface occur at much higher temperatures than were used in the ALL-MBE growth process. This is supported by cross sectional TEM images which do not show any indication of atomic interdiffusion 25 .…”
Section: Discussionmentioning
confidence: 60%
“…Intermixing of Sr atoms into the LMO layer is not likely in these samples because the kinetics of atomic diffusion perpendicular to the surface occur at much higher temperatures than were used in the ALL-MBE growth process. This is supported by cross sectional TEM images which do not show any indication of atomic interdiffusion 25 .…”
Section: Discussionmentioning
confidence: 60%
“…Such techniques are potentially interesting to control the TMR in MTJs by means of interfacial engineering. They can also be used to stabilize new layered perovskite phases, such as cation-ordered epitaxial phases [22,23], unattainable in bulk materials. In view of their inherent anisotropy, such artificially ordered layered perovskites may exhibit systematic differences in their electronic and magnetic structure with respect to their bulk-alloy counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…In view of their inherent anisotropy, such artificially ordered layered perovskites may exhibit systematic differences in their electronic and magnetic structure with respect to their bulk-alloy counterpart. For example, in the case of the artificial layered La 2/3 Ca 1/3 MnO 3 system, corresponding to an (LaMnO 3 ) 2 /(SrMnO 3 ) 1 (001) superlattice with a period of two unit-cell layers of LaMnO 3 and one unit-cell layer of SrMnO 3 , a 20% decrease in T C was reported with respect to the solid-solution alloy [22].…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that the disorder in the ionic radius of the A-site cation has a profound effect on the average ordering temperature of bulk manganites, which often complicates the determination of how much strain contributes to phase separation in thin film samples [3,4]. Nevertheless, a recent comparison of solid-solution alloy and A-site ordered superlattice La 2/3 Ca 1/3 MnO 3 thin film samples on different substrates revealed that strain is more important than chemical disorder in stabilizing the mixed phase regime near the average ordering temperature [5]. To investigate further the role of the substrate in the phase separation of a thin film sample, it is interesting to work on a sample which is, in its bulk form, a prototype of a discontinuous transition.…”
mentioning
confidence: 99%